2008
DOI: 10.1111/j.1365-2648.2008.04769.x
|View full text |Cite
|
Sign up to set email alerts
|

Conscious surgery: influence of the environment on patient anxiety

Abstract: A b s t r a c tAims: i) To investigate anxiety arising from the experience of the clinical environment during surgery under local/ regional anaesthesia and, ii) to uncover the specific aspects patients find anxiety provoking and possibly dissuade them from opting for such anaesthesia.Background: Operating theatres have historical been designed for safe, efficient surgery on the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 57 publications
(75 reference statements)
2
38
0
9
Order By: Relevance
“…In contrast, some patients were very calm, appearing to have no anxieties about their surgery. Staff found that patients were worried in particular about the anaesthetic, a finding that resonates with Mitchell's studies on anxiety and local and general anaesthesia [36,39,40], and which appeared to be the most prominent fear on the day of surgery. Staff discussed how they addressed patients' needs, describing interventions that they applied to their perceptions of their patients' needs.…”
Section: Fears and Anxietiesmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, some patients were very calm, appearing to have no anxieties about their surgery. Staff found that patients were worried in particular about the anaesthetic, a finding that resonates with Mitchell's studies on anxiety and local and general anaesthesia [36,39,40], and which appeared to be the most prominent fear on the day of surgery. Staff discussed how they addressed patients' needs, describing interventions that they applied to their perceptions of their patients' needs.…”
Section: Fears and Anxietiesmentioning
confidence: 70%
“…Miner-Williams [34], for example, asserts that spiritual care can be given in a spiritual manner through establishing a caring relationship and practising the art of being present, listening and supporting the patient's beliefs and values and through making a connection with the patient. Connecting with the patient, particularly in times of stress has been identified as significant in supporting the patient to cope [35,36]. Among many other writers, Clarke [37] supports the fact that spiritual care is not to be separated from care, but that it is based on relationships with patients and within the context of providing for physical care needs.…”
Section: Holismmentioning
confidence: 99%
“…Patients who had previous positive experiences during contact with healthcare professionals appeared informed and well prepared for what would happen during surgery and therefore have a tendency to be less anxious (Gardner et al, 2005). According to Mitchell (2008) people who are to be operated on for the first time are the most anxious. This anxiety might be due to perceptions about what will happen in the operating theatre; fear of feeling pain when the anaesthesia is given and fear of pain in general are salient.…”
Section: Discussionmentioning
confidence: 93%
“…According to Mitchell (2008) a number of patients were noted as having high concerns when entering the operating theatre. They felt uncomfortable about the narrow operating table, the sounds of saws and drills, the temperature, the darkness of the rooms and the unfamiliar equipment.…”
Section: Discussionmentioning
confidence: 99%
“…Zjawisko lęku przedoperacyjnego może pojawić się pod wpływem obaw związanych z ryzykiem obudzenia się w trakcie operacji lub też nieobudzenia się w ogóle [22]. Implikować niepokój może również niechęć do zakrywania twarzy maską w czasie znieczulenia ogólnego czy też obawa przed igłami oraz brakiem kontroli nad ciałem [23]. Lęk pacjentów wielokrotnie wiąże się z przewidywaniem wystąpienia bólu pooperacyjnego.…”
Section: Podsumowanieunclassified